Contribution Of The Tourism Sector And Unemployment Rate To Economic Growth Pre To Covid-19 Recovery - Chandra Murti Dewi Widowati Hermajiwandini (LPPM ISNJ Bengkalis, 2023)
This study aims to analyze and show the influence of the number of tourist visits (NTV), the number of hotel occupancies (NHO), local revenue (LRV), the unemployment rate (UPR), and the proportion of informal employment (PIE) to economic growth (gross regional domestic product/GRDP) during the pre-pandemic period until the recovery period for the Covid-19 pandemic in Indonesia. This study uses a quantitative method of panel data regression models. The data source uses secondary data in the form of documentation from the central statistics agency regarding research variables for all provinces in Indonesia from 2019 to 2021. The research results show that NTV and UPR negatively and significantly affect GRDP. LRV and PIE have a positive and significant effect on GRDP. NHO does not affect GRDP. This research theoretically contributes to complementing existing theories and practically provides benefits as a reference for the government in increasing economic growth from existing factors.